The Economics of Symbolic Exchange - Dolgin, Alexander (Springer, 2017)
The book addresses the mechanisms of culture in the digital age. Its author, professor at Higher School of Economics, tackles a number of highly relevant issues: the modus operandi of culture in a market environment, the role of money in the process and some methods intended to help consumers in the choice of cultural goods which best meet their tastes in a situation of ever increasing commercial cultural output. The economics of symbolic exchange is a branch of economic science dealing with "personality resources" such as free time, attention, emotions, etc. At present, these assets are virtually unaccounted for, nor used, due to the inherent impossibility of their measurement. As a result, more often than not, the economic thought entering the field of culture proves quite helpless. The book provides ample factual evidence relating to a whole range of cultural markets: record industry, book publishing, fashion, network resources and others. Special mention is made of the "grey" segments of the economy, such as the role of pirates and illicit dealers, or the activities of semi-legal file sharing services enabling free downloads of music and video material in the cyberspace. These glimpses into the "grey" territory expose holes in the "white" markets and contest certain myths. The material collected in the book comes down to quite a novel outlook on numerous phenomena of contemporary culture. The key purpose of this work is to introduce into practice some new management tools which are essential for the success of any economic changes in the field of culture, including recommendatory services operating as a social institution of expert consumer analysis of cultural goods and services.